Longer term stroke risk in intracerebral haemorrhage survivors. Issue 8 (17th June 2020) - Banerjee, Gargi; Wilson, Duncan; Ambler, Gareth; Hostettler, Isabel Charlotte; Shakeshaft, Clare; Cohen, Hannah; Yousry, Tarek; Al-Shahi Salman, Rustam; Lip, Gregory Y H; Houlden, Henry; Muir, Keith W; Brown, Martin M; et al.
Abstract : Objective: To evaluate the influence of intracerebral haemorrhage (ICH) location on stroke outcomes. Methods: We included patients recruited to a UK hospital-based, multicentre observational study of adults with imaging confirmed spontaneous ICH. The outcomes of interest were occurrence of a cerebral ischaemic event (either stroke or transient ischaemic attack) or a further ICH following study entry. Haematoma location was classified as lobar or non-lobar. Results: All 1094 patients recruited to the CROMIS-2 (Clinical Relevance of Microbleeds in Stroke) ICH study were included (mean age 73.3 years; 57.4% male). There were 45 recurrent ICH events (absolute event rate (AER) 1.88 per 100 patient-years); 35 in patients presenting with lobar ICH (n=447, AER 3.77 per 100 patient-years); and 9 in patients presenting with non-lobar ICH (n=580, AER 0.69 per 100 patient-years). Multivariable Cox regression found that lobar ICH was associated with ICH recurrence (HR 8.96, 95% CI 3.36 to 23.87, p<0.0001); similar results were found in multivariable completing risk analyses. There were 70 cerebral ischaemic events (AER 2.93 per 100 patient-years); 29 in patients presenting with lobar ICH (AER 3.12 per 100 patient-years); and 39 in patients with non-lobar ICH (AER 2.97 per 100 patient-years). Multivariable Cox regression found no association with ICH location (HR 1.13, 95% CI 0.66 to 1.92, p = 0.659). Similar results were seen in completing risk analyses. Conclusions: In ICH survivors, lobar ICH location was associated with a higher risk of recurrent ICH events than non-lobar ICH; ICH location did not influence risk of subsequent ischaemic events. Trial registration number: NCT02513316 .